Parent-Child Role Confusion: Exploring the Role of Family Processes in the Context of Parental Depression. Issue 6 (2nd November 2022) - DiMarzio, Karissa; Parent, Justin; Forehand, Rex; Thigpen, Jennifer Champion; Acosta, Juliana; Dale, Chelsea; Compas, Bruce
ABSTRACT: Objective: Parent-child role confusion has been shown to influence developmental outcomes for children whose parents have a history of depression; however, more research is needed to understand the pathways by which parental depression increases risk of role confusion. The current study aimed to extend previous literature by evaluating how different family processes (e.g., interparental conflict, guilt induction, family cohesion, and positive parenting practices) contribute to the development of emotional role confusion in families with a history of parental depression. Method: The sample was comprised of 90 parent-child dyads (parent M age  =  42, 90% female, 83.3% White; child M age  = 11.51, 51.1% female, 75.6% White) participating in the control group of a randomized controlled trial. All parents had a history of depression. A longitudinal path analysis was conducted to evaluate prospective associations in the multiple mediator model. Results: Findings from the current study suggest that parental depressive symptoms are not directly related to the development of parent-child emotional role confusion, but are instead indirectly related through increased interparental conflict observed by youth. Although not identified as significant mediators, guilt induction and positive parenting practices emerged as predictors of emotional role confusion. Lastly, family cohesion did not appear to influence the development of role confusion. Conclusion: Findings suggest that parenting behaviors and coparenting relationship quality play important roles in the development of parent-child emotional role confusion, with interparental conflict emerging as the strongest predictor in families with a history of parental depression.